Understanding Social Change in the Perspective of Da'wah on the Thought of Mohammad Natsir - Rini Setiawati; Mubasit Mubasit; Suslina Suslina; Umi Rojiati; Umi Aisyah (MUHARRIK: Jurnal Dakwah dan Sosial, 2021)
Mohammad Natsir is a figure of social change in strategic proselytizing thinking with its theory in its implementation. From this perspective, the thought of Mohammad Natsir finds his willingness to be appointed and analyzed. The method used is a descriptive analysis, and the data for writing this article is relevant literature. The study results found that in his proselytizing perspective, Mohammad Natsir's thoughts on the Concepts and Strategies of Social Change were: firstly, determining the purpose and function of da'wah is as shuhadā' 'alā al-nās, being a pioneer and overseer for the ummah of man and delivering man to the ultimate purpose of life, which is to worship God. Secondly, prepare a good da'wah or agent of social change to achieve perfection in da'wah's purpose. Natsir explained that a da'i must master Tafaqquh fī al-Dīn and Tafaqquh fī al-Nās. Thirdly, wisdom is the most excellent proselytizing method applied among other methods. According to Natsir, wisdom is more than mere science. It is nutritional science that has been digested and blends with a sense of check to become a driving force to make social change.